BIOENSAIOS POR INGESTÃO E MODOS DE AÇÃO DE INSETICIDAS PARA CARACTERIZAR SUSCETIBILIDADE E RESISTÊNCIA DOS PERCEVEJOS Euschistus heros E Dichelops melacanthus - Wagner, Fernanda Osmara (2017)
Soybean is one of the most cultivated crops in the country, and the stink bugs of the largest losses in productivity. The Neotropical brown stink bug Euschistus heros cause severe damage to soybeans, however the green belly stink bug Dichelops melacanthus cause severe damage to corn and wheat, and can also attack soybeans. For its control, seed treatment can be performed, as in the case of D. melacanthus, or sprays with insecticides. The objective of this work was to determine the feasibility of conducting ingestion biossays in E. heros and D. melacanthus, as well as to determine the mode of action of the insecticides used to control the E. heros stink bug. The feasibility of ingestion bioassays on E. heros and D. melacanthus with systemic inseticides was investigated, as well a topical bioassay with synergistic substances on E. heros to determine the mode of action of the most common recommended insecticides. The insects used in the bioassays were collected in Cândido Mota-SP, Palmital-SP, Pedrinhas Paulista-SP and Sertaneja-PR. The data obtained were analyzed by ANOVA and Probit analysis. The CL50 for E. heros for the thiametoxam + lambda cyhalothrin mixture was (0.038 + 0.028 μg iamL-1) and for D. melacanthus (0.219 + 0.164 μg de i.a.mL-1). In ingestion trials, this mixture achieved high mortality compared to the other active ingredients tested. When inoculation with the insecticide thiametoxam and the synergist piperonyl butoxide (PBO) agent was performed, the mortalities were significantly higher in the four populations tested indicating that the monooxygenases would be detoxifying the insecticide. Likewise, imidacloprid caused higher mortality when applied with the same synergist, indicating detoxification by monooxygenase enzymes. In the same way, treatments with pyrethroids (lambda-cyhalothrin and beta-cyfluthrin) and PBO caused higher or faster mortalities than the insecticide applied alone. When treatments with acephate and acephate plus diethyl maleate were performed, E. heros mortalities were faster with the synergist diethyl maleate, indicating detoxification of the insecticide by glutathione-S-transferases enzymes, mainly in the population of Sertaneja-PR.